Factors influencıng outsourcing of accounting services in Kazakhstani companies - Baimukhamedova, A.M.; Aimurzinov, M.S.; Baimukhamedova, G.S.; Isaeva, N.N. (BUKETOV BUSINESS REVIEW, 2023)
Object: Outsourcing of accounting services has significantly influenced the finance and accounting industry in recent decades. This research analyzes the determinants of outsourcing of accounting services in Kazakhstan companies. Methods: Correlation and logistic regression analysis were used in the study. Findings: This research examined the overall situation of outsourcing and how it has affected the performance of companies. Conclusions: The research conducted created a framework for analyzing accounting outsourcing. The analysis of variables and how they influenced the decision to outsource or not outsource accounting tasks in their organization provides concise and useful information on the assessment of the importance of the accounting process in companies. In addition, the study also points to the relationship between the intensity of accounting outsourcing in the preparation of financial statements and the performance of companies as measured by the return on assets and the companies’ leverage ratio. According to the results, it was found that there is no relationship between these two variables.